C.T Scan Measurements of the Lateral and Third Ventricles in Apparently Normal Iraqi Subjects - Jaumah, Zauhair A.; AL-Kafhaji, Fadhil A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Cerebral ventricular enlargement has been associated with many neurological disorders. Whether this enlargement is primary or secondary to these pathological conditions remains controversial. To define such enlargement, one must have measurements in normal subjects (controls).Patients and methods: One hundred-twelve (66 male and 46 females) apparently healthy normal subjects, with age ranging between 10-69 years were subjected to C. T scans as part of routine diagnostic workup for complaint of headache or recent minor motor-vehichle accident The ratio (measured as percent) of the ventricular-cross area of the lateral ventricle The maximum width (MTW) of the third ventricle was also determined. The data collected .was statistically analyzed.Results: Measurements of VBR ratios and MTV in both males and females of the normal groups revealed no significant difference. No significant difference in VBR ratio and MTW was noticed till the age of 49 years. Significant differences were noticed between 49-69 years of age.Conclusion: Abnormalities of the cerebral ventricular sizes are more easily identified in the Young than that found in old persons.